The neutrophil extracellular traps as a component of the tumor microenvironment - Е. V. Kayukova; E. V. Fefelova (Фундаментальная и клиническая медицина, 2020)
The stem cell mutations and modification of the tumor microenvironment are the main causes of cancer formation. The neutrophiles extracellular traps (NETs) are the components of the tumor microenvironment. NETs are web-like structures composed of nucleic acids, enzymes, cytoplasmic proteins, and bound pathogens. Currently the information on the pathogenetic role of NETs in the development of chronic noncommunicable diseases is contradictory. There is data of their carcinogenic effect. Aim. To determine the amount of NETs and the composition of the tumor microenvironment in the cervical smears in patients with precancerous diseases and cervical cancer. Material and Methods. The clinical group 1 - patients with precancer cervical diseases (n=10), the clinical group 2 – patients with cervical cancer III stage (n=14) were studied. The average age of patients was 38±8.26. The control group was formed of volunteers without cervical pathologies (n=10). Cervical smears were used as the material for the research. The study was compliant with the principles of WMA Declaration of Helsinki, 1964, rev. 2013 and was performed with consent of the Local Ethics Committee of Chita State Medical Academy. Cancer or dysplastic cells, normall cells, immune cells, NETs were counted in Feulgen stained cervical smears by the optical microscope. Results. There are reducing the proportion of healthy epithelial cells, increasing the pool of immune system cells and the appearance of the NETs in the cervical scraping during cervical cancerogenesis. NETs were visualized In 60% of cervical cancer patients. The statistically significant differences in the content of NF in cervical smears among the group of patients with precancerous diseases of the cervix and the control group did not determinated.Conclusion. Detection of the NETs in the cervical smears may be a new cytological sign of malignancy of the cervical epithelium. Detection of the NETs in the cervical tumor microenvironment smears may indicate their involvement in cervical carcinogenesis.